T TABASSUM Nov 2012 2 0 LONDON Nov 3, 2012 #1 Hi can anyone explain how i can get express Fn+3 in terms of Fn+2 and Fn to show that Fn+2 = 1/2(Fn+3 + Fn). Any help is much appreciated

Hi can anyone explain how i can get express Fn+3 in terms of Fn+2 and Fn to show that Fn+2 = 1/2(Fn+3 + Fn). Any help is much appreciated

MarkFL Dec 2011 2,314 916 St. Augustine, FL. Nov 3, 2012 #2 I would begin with: (1) \(\displaystyle F_{n+2}=F_{n+1}+F_{n}\) (2) \(\displaystyle F_{n+3}=F_{n+2}+F_{n+1}\) Now, solve (2) for \(\displaystyle F_{n+1}\) and substitute into (1), then solve for \(\displaystyle F_{n+2}\). Reactions: 1 person

I would begin with: (1) \(\displaystyle F_{n+2}=F_{n+1}+F_{n}\) (2) \(\displaystyle F_{n+3}=F_{n+2}+F_{n+1}\) Now, solve (2) for \(\displaystyle F_{n+1}\) and substitute into (1), then solve for \(\displaystyle F_{n+2}\).